Deskripsi Gerak dan Lagu Pada Anak Usia 5-6 Tahun - R. Amasi, Rahmatillah; Laiya, Sri Wahyuningsi; Rawanti, Sri (JURUSAN PENDIDIKAN GURU PENDIDIKAN ANAK USIA DINI, 2024)
This research aims to describe the movement and songs of Group B children at TK Cempaka Kindergarten in Batudaa District, Gorontalo Regency. This descriptive research used a survey method with data collection techniques involving a questionnaire. The population and sample consisted of 24 Group B children from TK Cempaka Kindergarten in Batudaa District, Gorontalo Regency. The instrument was a questionnaire, and data analysis was conducted descriptively in percentage form. Based on the analysis, it was found that (1) the percentage of Movement and Songs in Group B children at TK Cempaka Kindergarten in Batudaa District, Gorontalo Regency, based on developmental indicators, showed that children were able to recognize body parts through movement and songs such as